What lessons have been learnt since the East Asian Crisis in 1997/98? CIBS, capital flows and exchange rates - Marion Pircher (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
This paper discusses the movement of capital flows to and from the exchange rate regimes and monetary policies of China, India, Brazil, and South Africa (CIBS). Furthermore, we compare the level of financial stability, and the composition and duration of capital flows of the countries on a policy level according to the - third generation crisis models'; following which the East Asian Crisis of 1997/98 linkages between the corporate and financial sectors, and foreign short-term debt are given further attention. The paper concludes by comparing all four countries and analysing possible risks in CIBS financial systems.
Keywords: F32; G15; N20; 330; international financial markets; financial stability; capital flows; exchange rates; China; India; Brazil; South Africa; Internationaler Finanzmarkt; Finanzmarktkrise; Kapitalmobilität; Wechselkurssystem; Geldpolitik; China; Indien; Brasilien; Südafrika